Manifestações do insólito na escrita de Silvina Ocampo : uma análise de contos ocampianos publicados na revista Sur - Carniel, Morgana (My University, 2023)
This study investigates how the writing of Silvina Ocampo, in the short stories "La siesta en el cedro" (1936), "Autobiografia de Irene" (1944) and "El Médico charme" (1960), published in the Argentine periodical Sur, contributes for the manifestation of a new perspective of the fantastic, in the scenario of Latin American literature of the 20th century, and how the periodical in question allows the visualization of the different phases of the author's writing in these short stories. The investigation also allows us to understand the relevance of the author's writings, in the fantastic, as an important instrument in the expansion of fantastic literature, beyond the usual limits of the traditional todorovian fantastic. The articulation of the fantastic with the press makes it possible to understand the importance of the periodical Sur in the dissemination of Silvina Ocampo's work, since Sur not only operated as a vehicle for disseminating Silvina's works, but also decisively influenced the author's way of writing, as verified by the analysis of the stories in question. In order to fulfill the intended objective, the theoretical approach was based on the fantastic and neo-fantastic literature, and studies about the work of Silvina Ocampo, based on the theories of Filipe Furtado (1980), Tzvetan Todorov (1992), Jaime Alazraki (1990), David Roas (2014), Rosalba Campra (2016), Judith Podlubne (2012), Mariana Enriquez (2018), Natália Biancotto (2015; 2019) and others. [resumo fornecido pelo autor]
Este estudo investiga de que modo a escrita de Silvina Ocampo, nos contos "La siesta en el cedro" (1936), "Autobiografia de Irene" (1944) e "El médico encantador" (1960), publicados no periódico argentino Sur, contribui para a manifestação de uma nova perspectiva do fantástico, no cenário da literatura latino-americana do século XX, e em que medida este periódico possibilita a visualização das diferentes fases da escrita da autora nestes contos. Tal investigação também permite compreender a relevância dos escritos da autora, no quadro do fantástico, como um importante instrumento na expansão da literatura fantástica, para além dos habituais limites do fantástico tradicional teorizado por Todorov. A articulação do tema fantástico com a imprensa possibilita a compreensão da importância do periódico Sur na divulgação do trabalho de Silvina Ocampo, visto que a Sur não apenas operou como veículo de disseminação das obras de Silvina, mas também influenciou decisivamente a forma de escrita da autora, conforme verificou-se pela análise dos contos em pauta. Para cumprir o objetivo proposto, dispôs-se de aporte teórico oriundo sobretudo do fantástico e do neofantástico literário, e de estudos acerca da obra de Silvina Ocampo, a partir das teorizações de Filipe Furtado (1980), Tzvetan Todorov (1992), Jaime Alazraki (1990), David Roas (2014), Rosalba Campra (2016), Judith Podlubne (2012), Mariana Enriquez (2018), Natália Biancotto (2015; 2019) e outros. [resumo fornecido pelo autor]
Keywords: Literatura argentina - Crítica e interpretação; Mulheres na literatura; Literatura fantástica; Ocampo, Silvina, 1903- 1993; Argentine literature - Criticism and interpretation; Women in literature; Fantasy literature